Responder coordenado sob esquema de Razão Variável (VR) em ratos - Souza, Lucas Codina (2023)
Cooperation between two or more organisms has been experimentally shown to be susceptible to selection by consequences similarly to individual operant behavior. Previous studies in the Laboratory of Psychology of Learning at UFSCar observed the establishment of temporally coordinated responses as a type of cooperation in pairs of rats and investigated the ways in which responding is distributed under fixed ratio (FR) and variable ratio (VR) schedules of reinforcement with equal parameters (FR10, VR10) and with parametric variations of ratio size (FR). In these studies, the consequence was only produced when the two rats emitted responses that were defined as coordinated, and the schedules generated patterns of coordination that were similar to patterns that were observed with the behavior of individual organisms when they were subjected to the same schedule types and parameters. The individual response pattern of each member of the pair was less regular than the coordination pattern, suggesting that the programmed contingency resulted in the selection of coordinated behavior as an operant unit. These were the first studies that used intermittent schedules to investigate coordinated responding. The replication of typical patterns of responding under other schedules of reinforcement may provide new evidence of cooperation as an operant unit and contribute to verifying the relevance and generalizability of this concept. The present study investigated effects of parametric manipulations of ratio size under a VR schedule on coordinated responses of pairs of rats. The coordination criterion was defined as simultaneous lever pressing (t < 0.5 s) by both animals of each pair. The control condition investigated lengthening the cooperative criterion from 0.5 s (A) to 5 s (B) in an ABABA design under a VR 9 schedule (one of the parametric series values). The study also evaluated the extinction of coordinated behavior and effects of shortening the duration of light that was used as feedback for coordinated responses. The results showed the establishment of an inverted U-shaped function between ratio size and behavior (i.e., rates and proportions of coordinated responses). Independent responses that did not belong to cooperative episodes did not systematically change as a function of ratio size. Manipulating the duration of the interval for coordination resulted in rates and proportions of coordinated responses that were greater at 0.5 s than at 5 s. Extinction led to a reduction of individual and coordinated responding but generated variability between the pairs in terms of the initial effect, which sometimes focused on independent responding and sometimes on coordinated responding. These findings indicate that the coordinated VR contingency more directly favored the selection of coordinated responses than individual responding, generating typical patterns of the operant that were maintained under a VR schedule. The results extend generalizability of the effect of reinforcement schedules on coordinated responses of pairs of rats and highlight methodological aspects that should be evaluated in future research.